Exploring the underpinnings of pseudo-prostitution in institutions of higher learning in selected African countries: a literature review - Mafa, Itai; Kang’ethe, S.M. (Kamla-Raj Enterprises, 2020)
Indubitably and regrettably, pseudo prostitution is a cankerworm that needs to be fought right, left and down the middle in institutions of Higher learning of especially developing countries. This is believed to be a result of poverty and its concomitant ramifications. Through the use of a review of literature methodology, the aim of the paper is to explore factors surrounding pseudo prostitutions in institutions of Higher learning in some developing countries. The following factors were found to underpin the phenomenon: poverty and lack of a viable financial support system; sexual permissiveness; cultural fusion; and peer media pressure and sexuality. The following perfidious and ramifying factors have been associated with the phenomenon. Prevalence of STDS; the dangers of backstreet abortion; loss of academic focus; and passion related crimes. The paper recommends: sufficient financial assistance and income plan of students especially the girl children by relevant stakeholders; moral restoration through the facilitation of FBO in institutions of Higher learning; desensitizing the sex subject; improved edutainment campaigns on STD and drug and alcohol abuse; tightening the residence access control; proving sufficient entertainment activities. The Moral Development Theory has been found befitting in analysing the birth and perpetuation of pseudo-prostitution in tertiary institutions.